Analysis of ABC Method, EOQ Method and Safety Stock as Determinants of Inventory Control Optimization of Tobacco Products Sumber Jaya at Jamsbacco Store - Kharina, Eliza Febi (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research focuses on product grouping using the ABC method, analyzing and evaluating product inventory control using the Economic Order Quantity (EOQ) and Safety Stock methods, in order to improve the efficiency and effectiveness of managing product inventory at Jamsbacco stores. Design/Method/Approach : This research is a quantitative method research with case study techniques. This research focuses on an in-depth analysis of a unique or specific case, with the aim of understanding in detail the phenomenon, process, or behavior in a particular context, especially in the business field. The subject of this research is the Jamsbacco Tobacco Shop which is located at Tunggul Wulung Street, Karangrejo Village, Ngasem District, Kediri Regency. The object of this research is the inventory of trade goods in the form of TIS Tobacco brand Sumber Jaya. Research Finding : : There are not many studies that discuss inventory control in tobacco retail stores Theoretical contribution/Originality : Could be useful for tobacco product control Practitionel/Policy implication : The limitations of this research focus on specific products in inventory control optimization analysis so that it often causes strategic limitations. Research limitation : The limitations of this research focus on specific products in the analysis of inventory control optimization so that it often causes strategic limitations.